Herbicides in Brazil: a brief review (Research, Society and Development, 2020)
In Brazil, the use of pesticides has been growing year after year, due to the fact that much of the agricultural production system is conventional, which leads to the intensive use of these products. With the increase in consumption, many farmers, because they do not have access to the necessary information, do not prevent themselves at the time of application of the product, and dispose of the packaging improperly, causing greater risks of human and environmental contamination. Making use of a case study based on data collected from competent agencies and companies, this study aims to evaluate the use of herbicides for the management of weeds in pastures and thus verify that this is the most efficient and economical way to control of these plants that compete with forages in nutrients, space, light and water. By identifying the type of weed it is possible through the appropriate herbicide to have a control of the action of the weeds and thus recover pasture areas.